2003
DOI: 10.1038/sj.bmt.1704040
|View full text |Cite
|
Sign up to set email alerts
|

Why aren't we performing more allografts for aggressive non-Hodgkin's lymphoma?

Abstract: Summary:Allogeneic stem cell transplantation has an underappreciated role in the management of intermediate-grade non-Hodgkin's lymphoma. It provides several advantages over autologous stem cell transplantation including provision of a lymphoma-free graft, reduced rates of secondary myelodysplastic syndrome and leukemia, and a potentially curative graft-versus-lymphoma effect. When applied to chemosensitive patients, the lower relapse rates and reasonable long-term outcomes make allogeneic transplantation a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…[27][28][29] Further, the monoclonal antibody rituximab has the potential to improve the treatment results in relapsed or refractory B-cell lymphoma on several levels; first, at initial cytoreductive treatment for rapid induction of remission, second, for in vivo stem cell purging, and lastly, during or after HDT for the maintenance of remission. [30][31][32] In conclusion, the feasibility to include treosulfan into a high-dose combination regimen has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Further, the monoclonal antibody rituximab has the potential to improve the treatment results in relapsed or refractory B-cell lymphoma on several levels; first, at initial cytoreductive treatment for rapid induction of remission, second, for in vivo stem cell purging, and lastly, during or after HDT for the maintenance of remission. [30][31][32] In conclusion, the feasibility to include treosulfan into a high-dose combination regimen has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous HCT, however, is less effective in patients with chemoresistant relapse (1013). This observation often is explained by an increase in relapse risk due to a lack of graft-versus-lymphoma effect and because of re-infusion of malignant cells (4, 5, 1416). Allogeneic HCT, usually employing bone marrow as the stem cell source, is a potential therapeutic option especially for patients with matched sibling donors and higher risk disease.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative trials of autologous versus allogeneic SCT presents some selection bias because usually patients enrolled in allograft cohort have more advanced disease, more prior therapies and/or bone marrow involvement. However, these studies demonstrated that allografting induced a lower relapse risk as compared with autologous SCT, but the high NRM offset any survival benefit [29]. In a retrospective study Rodriguez et al evaluated the outcome of patients receiving autologous (n ¼ 29) or allogeneic SCT (n ¼ 7) for PTCL: the 3-year overall survival was 39% and 29%, respectively.…”
Section: Allogeneic Stem Cell Transplantationmentioning
confidence: 94%